Obstoj odsotnosti pravnega vrastva v tehnološko razviti industriji - Murtič, Sašo (Perfectus AC, 2019)
Through the processes of development of Industry 4.0 and the increasing implementation of Industry 5.0, advanced technology is being developed, which is increasingly taking over individual tasks and processes in direct industrial production, and this stage of development is increasingly present in the service industry. We are recognizing more and more interconnected systems, procedures and processes, which are being taken over by smart technology with software management. It is a period when the new technology with its use causes severe international economic and trade competition, rapid changes in production, increasing digitalization of production and other processes and robotization of individual production and service activities. There is a coexistence of natural and artificial intelligence, there is a growing need to invest in technology, and there is no care for employees, who, despite development, are an important element of industry and the economy. To all these findings, the purpose of the research was to ask how technology affects employees and what is the legal security of employees in the smart industry. For these needs, we studied the individual elements of the introduction of smart machines and devices in the processes of industrial production and service activities, looking for elements of the position of the worker, and found that the results can be interpreted differently. At the same time, we were looking for appropriate solutions that would justify the use of 4.0 technology and the reorientation of work to industrial development 5.0, while trying to find legal protection for employees.
Keywords: artificial intelligence; coexistence; legal protection; naravna inteligenca; natural intelligence; pravno varstvo; sožitje; technology; tehnologija; umetna inteligenca